2005
DOI: 10.1063/1.1847391
|View full text |Cite
|
Sign up to set email alerts
|

Element-specific magnetic properties of Co2MnSi thin films

Abstract: Co 2 MnSi thin films were grown on Al 2 O 3 ͑a plane͒ and GaAs ͑001͒ substrates and on thin silicon nitride windows using pulsed laser deposition. Angle-dependent magneto-optic Kerr effect measurements reveal both a uniaxial and a fourfold magnetocrystalline anisotropy for films grown on GaAs ͑001͒. X-ray magnetic circular dichroism spectra were measured at the L 2,3 edges of the thin films as a function of aluminum cap layer thickness, and transmission mode L 2,3 x-ray absorption through a 1000-Å Co 2 MnSi fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The intensity of these shoulders increases dramatically with annealing temperature and thus correlates with the degree of L2 1 ordering determined by XRD. These features were seen before in the Co L 2,3 absorption spectra from L2 1 ordered Heusler films, 13,15,16 although their origin remained so far unexplained.…”
Section: A Interfacial Site Disordermentioning
confidence: 92%
See 1 more Smart Citation
“…The intensity of these shoulders increases dramatically with annealing temperature and thus correlates with the degree of L2 1 ordering determined by XRD. These features were seen before in the Co L 2,3 absorption spectra from L2 1 ordered Heusler films, 13,15,16 although their origin remained so far unexplained.…”
Section: A Interfacial Site Disordermentioning
confidence: 92%
“…To date there have been several studies that utilized these techniques to examine the interfacial properties of materials used in magnetic tunnel junctions. [8][9][10][11][12][13][14][15][16] Some of this work has focused on the Heusler-alloy-based MTJs, where the electronic and magnetic structure at the interfaces has been investigated for different sample preparations. [12][13][14][15][16] However, so far the roles of interface ordering and barrier oxidation on the HMF have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the shallow probing depths, these techniques are effective for study of the electronic and magnetic properties of interfaces, which play important roles in TMR devices. To date several studies have utilized these techniques to examine the interfacial properties of materials used in MTJs, [16][17][18][19][20][21][22][23][24] and some of them have focused on Heusler-alloy-based MTJs. Electronic and magnetic properties at interfaces have been investigated for various thicknesses in Co-rich Co 2 MnSi 25,26 and Co 2 MnGe 27 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Since the theoretical prediction of the first half-metallic material, 1 the half-Heusler alloy NiMnSb, many other Heusler alloy systems have been predicted to be half-metallic including Co 2 MnGe and Co 2 MnSi, and much experimental work followed. [2][3][4][5][6][7][8] It was found that many of the physical properties of these systems, including the degree of spin polarization, are diminished by physical occurrences in the system, the most common ones being forms of disorder including, primarily, antisite disorder, which has been observed experimentally. 9,10 For instance, it was predicted that Co antisite disorder in Co 2 MnSi introduced a finite contribution in the gap of the minority density of states, resulting in suboptimum spin polarization, i.e., far below the predicted values.…”
Section: Introductionmentioning
confidence: 99%